2012
DOI: 10.1111/papr.12013
|View full text |Cite
|
Sign up to set email alerts
|

0.025% Capsaicin Gel for the Treatment of Painful Diabetic Neuropathy: A Randomized, Double‐Blind, Crossover, Placebo‐Controlled Trial

Abstract: 0.025% capsaicin gel is safe and well tolerated, but does not provide significant pain relief in patients with PDN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 17 publications
0
32
0
3
Order By: Relevance
“…Some clinical trials have demonstrated the effectiveness of lowconcentration (from 0.025% to 0.075%) capsaicin cream in DNP [11,174,175] . Higher concentrations are not indicated because of desensitization of nociceptive sensory nerve endings, which may increase the risk of skin injuries in DNP patients [173,174] . Some adverse effects include itching, stinging, erythema, transient burning sensation and initial pain at the application site, that diminishes with repeated use [132,175] , leading many patients to withdraw from the treatment [128,173] .…”
Section: Others Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some clinical trials have demonstrated the effectiveness of lowconcentration (from 0.025% to 0.075%) capsaicin cream in DNP [11,174,175] . Higher concentrations are not indicated because of desensitization of nociceptive sensory nerve endings, which may increase the risk of skin injuries in DNP patients [173,174] . Some adverse effects include itching, stinging, erythema, transient burning sensation and initial pain at the application site, that diminishes with repeated use [132,175] , leading many patients to withdraw from the treatment [128,173] .…”
Section: Others Agentsmentioning
confidence: 99%
“…Higher concentrations are not indicated because of desensitization of nociceptive sensory nerve endings, which may increase the risk of skin injuries in DNP patients [173,174] . Some adverse effects include itching, stinging, erythema, transient burning sensation and initial pain at the application site, that diminishes with repeated use [132,175] , leading many patients to withdraw from the treatment [128,173] . Lidocaine patch: Lidocaine patches act as peripheral analgesics with minimal systemic absorption and are used in combination with other analgesic drugs [132,172] .…”
Section: Others Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical trials have also investigated the ability of a 0.025% capsaicin patch to decrease the pain associated with diabetic neuropathy [54]. Although the patch was well tolerated in patients, it provided no relief from pain.…”
Section: Advanced Drug Delivery Systemsmentioning
confidence: 99%